Analisia Hadis Penetapan Awal Bulan Kamariah (Ramadan dan Syawal) - Hajar, Hajar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Determining the beginning of Ramadhan and Syawal can do by rukyat, hisab and istikmal. Method of rukyat which done by Prophet Muhammad saw, friends, tabiin until now. Rukyat can do all off people with see the hilal when the sunset in the end of month. Hisab is calculating position and height of hilal at the sunset. If hilal can not seen because of weather so entire numbering of Syakban become 30 days. Determine like this can call with istikmal. Differentiate in determining beginning of Ramadhan and Syawal it’s happen because method of using is not same with determining height of hilal reputed new month also not same.